Emerging role of interleukin‐33 in autoimmune diseases. Issue 1 (January 2014) - Pei, Cheng; Barbour, Mark; Fairlie‐Clarke, Karen J.; Allan, Debbie; Mu, Rong; Jiang, Hui‐Rong
Summary Interleukin‐33 (IL‐33) is a member of the IL‐1 cytokine family. It predominantly induces type 2 immune responses and thus is protective against atherosclerosis and nematode infections but contributes to allergic airway inflammation. Interleukin‐33 also plays a pivotal role in the development of many autoimmune diseases through mechanisms that are still not fully understood. In this review, we focus on the recent advances in understanding of the expression and function of IL‐33 in some autoimmune disorders, aiming to provide insight into its potential role in disease development.